The Impact of the Heutagogy Approach on Responsibilities for Online Learning in Statistics Courses - Endang Mulyati Ningsih; Ngabdul Munif; Sugiyono Sugiyono (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2022)
This study aims to determine: (1) learning responsibilities and; (2) positive, negative and accompaniment impacts that occur after learning statistics using the heutagogy approach. This study uses an impact evaluation method with a goal free evaluation model. The population of this study was 104 students who took the Statistics course in the Odd Semester 2020. The sample was selected using a systematic technique as many as 82 students. The research data were collected from grades and assignments documents, interviews and learning responsibility questionnaires. The quality of the instrument was controlled using item validity and reliability with a halving technique. The validity of the qualitative data was controlled by means of document triangulation and interviews. The results showed: (1) the highest learning responsibility was in the learning effort, followed by discipline, independence, motivation and honesty; (2) the positive impact is felt by students in the upper group because they are more successful in learning anytime and anywhere, the negative impact is felt by the lower group because it opens up opportunities to look for examples of friends' answers. The impact of the accompaniment is that there is cooperation in the face of difficulties